2016
DOI: 10.1037/tra0000063
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for DSM–5 posttraumatic stress symptoms (PTSS) among Israeli civilians during the 2014 Israel-Hamas war.

Abstract: In light of current modifications in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) diagnostic criteria for posttraumatic stress disorder (PTSD), this study aimed to revalidate well-known PTSD risk factors related to terrorism and war in Israel, namely, proximity to the Gaza Strip, dissociative symptoms, acute stress disorder (ASD) symptoms, and social support. One hundred and sixty Israeli civilians were assessed during the 2014 Israel-Hamas war at 2 time points: 1 week a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Israeli civilians living in Israel's Southern region. This sample was divided into three groups, based on proximity to the Gaza strip: a) lived 4-25 miles from the border; b) lived 25-50 miles and c) lived more than 51 miles away from the border (Gil et al, 2015). The study's findings confirmed the significance of ASD symptoms identified a week after traumatic exposure as the hallmark risk factor for a subsequent development of PTSD at one month.…”
Section: Posttraumatic Stress Disorder Death Anxiety and Secondary supporting
confidence: 53%
See 1 more Smart Citation
“…Israeli civilians living in Israel's Southern region. This sample was divided into three groups, based on proximity to the Gaza strip: a) lived 4-25 miles from the border; b) lived 25-50 miles and c) lived more than 51 miles away from the border (Gil et al, 2015). The study's findings confirmed the significance of ASD symptoms identified a week after traumatic exposure as the hallmark risk factor for a subsequent development of PTSD at one month.…”
Section: Posttraumatic Stress Disorder Death Anxiety and Secondary supporting
confidence: 53%
“…The study's findings confirmed the significance of ASD symptoms identified a week after traumatic exposure as the hallmark risk factor for a subsequent development of PTSD at one month. Previous studies showed that approximately 70% of trauma survivors who initially met criteria for ASD also met criteria for PTSD (Brewin, Andrews, & Valentine, 2000;Frans, Rimma, Aberg, & Fredrikson, 2005;Johnson, Maxwell, & Galea, 2009 (Gil et al, 2015).…”
Section: Posttraumatic Stress Disorder Death Anxiety and Secondary mentioning
confidence: 99%
“…Fortunately, geographically proximity to Gaza did not show any association with PTSD. Conceivably, the war condition and the reality that large areas of Israel that were under constant missile attacks, created uncertainty regardless of the variations in distance (Gil et al 2015).…”
Section: Post-trauma C Stress Disorder and Acute Stress Disorders Andmentioning
confidence: 99%
“…Th e defi nition of national terrorism suggests some of its consequences for the targeted population: loss of life, injuries and increased anxiety and fear. Studies conducting with victims of direct national terror attacks (i. e., survivors, witnesses and close relatives of those who were killed) confi rm that these individuals are at high risk of suff ering from a distress reaction (Solomon, Mikulincer, Waysman, Marlowe 1991;Gidron 2002;Shalev, Tuval-Mashiach 2005;Ron, Shamai 2015). Th e distress symptoms include generalized fear and anxiety, recurrent thoughts about the terror attack, avoidance behavior, physiological symptoms, depression, problems in daily functioning, and diffi culties in relating to trusting others.…”
Section: The Impact Of Terrorism Military Opera Ons and Warsmentioning
confidence: 99%
See 1 more Smart Citation